PENGEMBANGAN MEDIA DAN MODUL BERDIFERENSIASI DI SMA DARUL HIJRAH PUTERI MARTAPURA - Rusiani, Risda (FTIK UIN Sultan Aji Muhammad Idris Samarinda, 2025)
The development of differentiated learning media and modules at SMA Darul Hijrah Puteri Martapura was carried out to accommodate students’ diverse potentials, interests, and learning styles, as well as to enhance the effectiveness of the learning process. The activity included needs analysis through diagnostic assessment, formulation of learning objectives, product development (printed modules such as lesson plans and student worksheets, interactive presentations using PowerPoint and Canva, and digital media), classroom implementation, and collaborative evaluation and reflection between teachers and students. The program involved the principal, vice principal for curriculum, teaching staff, educational personnel, and students. The results showed that the differentiated media and module packages were well-received by both teachers and students, leading to increased motivation, comprehension, independence, creativity, and active participation in learning. The main challenges included limited teacher skills in instructional design and inadequate learning facilities. Recommendations include providing further training for teachers, improving school infrastructure, and continuing innovation to ensure sustainable implementation of differentiated learning that supports the profile of adaptive learners.